2014
DOI: 10.1016/s0049-3848(14)50024-2
|View full text |Cite
|
Sign up to set email alerts
|

Insights into platelet-based control of coagulation

Abstract: The coagulation process is activated by tight control mechanisms, in which platelets play prominent and unique roles. In thrombosis and hemostasis, activated platelets regulate the coagulation system in various ways: by exposing a phosphatidylserine surface for thrombin formation, by supporting fibrin formation, and by regulating the retraction of a fibrin clot. In this review we discuss the involvement of platelet receptors, other membrane proteins, downstream signaling proteins, cytoskeleton-linked proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 118 publications
3
58
0
1
Order By: Relevance
“…Our in vitro and in vivo analyses of thrombus formation induced by TMEM16F-null platelets suggested a role for TMEM16F in activation-induced PtdSer exposure, and supported the model in which Ca 2+ -induced PtdSer exposure is involved in the generation of thrombin and fibrin, but not clot retraction (16,17). Mice with the platelet-specific deletion of TMEM16F exhibited a phenotype similar to that of human patients with Scott syndrome, and may provide a useful model for this human disease.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…Our in vitro and in vivo analyses of thrombus formation induced by TMEM16F-null platelets suggested a role for TMEM16F in activation-induced PtdSer exposure, and supported the model in which Ca 2+ -induced PtdSer exposure is involved in the generation of thrombin and fibrin, but not clot retraction (16,17). Mice with the platelet-specific deletion of TMEM16F exhibited a phenotype similar to that of human patients with Scott syndrome, and may provide a useful model for this human disease.…”
supporting
confidence: 74%
“…Notably, Yang et al (13) activated mouse platelet at 37°C for 30 min and did not see clear TMEM16F dependency on PtdSer exposure. PtdSer exposure in activated mouse platelets is also mediated by cyclophilin D-dependent Ca 2+ -induced openings of the mitochondrial permeability transition pore (MPTP) (17,32). These changes in MPTP lead to cell death, and mouse platelets may undergo MPTP more easily than human platelets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both Atg5 and Beclin 1 are essential for apoptotic cell clearance during development by mediating expression of extracellular PS. 73 As PS exposure is also important for hemostasis, 74,75 we thought that autophagy-mediated PS exposure in platelets might be required for hemostasis. Unfortunately, this hypothesis is unlikely, as our studies with annexin V (data not shown) and lactadherin (supplemental Figure 5E) binding showed no impairment in activation-dependent PS exposure on Atg7 f/f ;PF4-Cre/1 platelets.…”
Section: Autophagy In Hemostasis and Thrombosis 1229mentioning
confidence: 99%
“…In thrombolysis, Fibrinogen, a prime protein causes fibrinolysis. It is soluble, complex multifunctional 340 kDa of 45 nm in length [2].…”
Section: Introductionmentioning
confidence: 99%